Tobacco Pack Information - World Bank (Washington, DC, 2012)
There are an estimated 1.2 billion regular smokers in the world today, approximately one third of the global population over the age of 15, and the numbers are rising (World Health Organization 2002). Studies show that many smokers still do not know that tobacco causes disease and premature death. Many others know little beyond a vague notion that "smoking is bad for you"- even in the US, where a great deal of information is easily available from multiple sources (USDHHS 1989). There is a clear need for effective ways to inform and alert smokers and provide information on how to reduce their tobacco-related health risks. Strongly worded, specific, large label information on tobacco product packages provides important public health messages, targeting smokers.